Dimensional Accuracy in Four Types of Type IV Die Stone After Delayed Pouring: A Comparative Study - Sriharsha Pudi; Arun Rosan David Raj; Hemamalini Balaji; Venkat Rengasamy; Priyanka Matsa; V Varun Anand (Journal of Pharmacy and Bioallied Sciences)
Background and Aim: Accurate dental casts are essential for various dental procedures. Type IV gypsum is commonly used due to its properties. However, delayed pouring may affect accuracy. This study evaluates the dimensional accuracy of four Type IV die stones at 1-hour and 24-hour pouring intervals. Methodology: Eighty samples were divided into four groups. Impressions were made using standardized procedures, and die stones were poured after 1 hour or 24 hours. Measurements were taken using a profile projector. Results: ZODENTA demonstrated the least variation at 1-hour pouring, while FUJI showed minimal variation at 24-hour pouring. Differences between 1-hour and 24-hour pouring were minimal across brands. Discussion: Type IV gypsum is favored for dental casts due to its properties. Other studies have explored related factors such as surface roughness and hardness. Conclusion: ZODENTA was more accurate at 1-hour pouring, while FUJI performed better at 24-hour pouring. Further research is needed to understand the impact of delayed pouring on dimensional accuracy in dental restorations.